1970
DOI: 10.1136/sti.46.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fatty acids of treponemes.

Abstract: EVIDENCE is rapidly accumulating which indicates that gas liquid chromatography (GLC) is a useful aid in the identification and classification of microorganisms (Abel, de Schmertzing, and Peterson, 1963; Reiner, 1965; Henis, Gould, and Alexander, 1966). Recently, several workers have analysed microorganisms for fatty acids by GLC and, by comparing their profiles, have established some useful taxonomic relationships (Moss and Lewis, 1967; Yamakawa and Ueta, 1964). The present study describes the fatty acid comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1970
1970
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…As part of the characterization of the freeliving anaerobic spirochetes, the fatty acid composition of Spirochaeta stenostrepta, cultivated in a medium which was not supplemented with serum, albumin, or fatty acids, was examined. The fatty acid composition of this organism consisted primarily of saturated branch-chained odd carbon number fatty acids which were dramatically different from that reported for other spirochetes (2)(3)(4)9). S. stenostrepta strain Z-1 (ATCC 25083) was cultivated on GYPT medium (5).…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…As part of the characterization of the freeliving anaerobic spirochetes, the fatty acid composition of Spirochaeta stenostrepta, cultivated in a medium which was not supplemented with serum, albumin, or fatty acids, was examined. The fatty acid composition of this organism consisted primarily of saturated branch-chained odd carbon number fatty acids which were dramatically different from that reported for other spirochetes (2)(3)(4)9). S. stenostrepta strain Z-1 (ATCC 25083) was cultivated on GYPT medium (5).…”
contrasting
confidence: 90%
“…Growth of leptospires in the presence of odd carbon number fatty acids resulted in a profile consisting mostly of saturated and unsaturated odd carbon number fatty acids (4). Branch-chained fatty acids were either not detected or were present in trace amounts in leptospires or treponemes (2)(3)(4)9), but represented 27 and 9% of the total fatty acid composition of Borrelia vincentii and Spirochaeta zuelzerae, respectively (2).…”
mentioning
confidence: 99%
“…In an effort to determine whether linoleic acid or trans-l1-octadecenoic acid was incorporated into cellular lipids, the spirochete was inoculated into medium containing linoleic acid-1-14C (5 MCi). After 14 hr of growth at 37 C, separate analysis of the cells and supernatant fluid obtained by centrifugation revealed that 63% of the recovered radioactivity was associated with the cells and 37% with the supernatant fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Cohen et al (5) have examined the cellular fatty acids of a number of pathogenic treponemes. Palmitic, stearic, 1 8-carbon monoenoic, and dienoic acids were the predominant fatty acids present.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the fatty acid composition of treponemes by gas chromatography (Cohen, Moss, and Farshtchi, 1970). Recent advances in the formation of derivatives have extended the use of gas chromatography to many compounds present in biological materials.…”
Section: Discussionmentioning
confidence: 99%